Aplikasi Sistem Diagnosa Penyakit pada Manusia yang Ditularkan oleh Vektor Nyamuk Menggunakan Metode Forward Chaining - Purba, Kevin Joel; Widiartha, I Made (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Disease is very easy to find in tropical countries including Indonesia. The skin itself is the most outermost organ that is easily attacked by the skin because the skin itself is an organ that is used to protect the internal organs. Many people do not consider how dangerous the skin disease is if it is not treated. Therefore, it is expected that with the advancement of technology, it can prevent the occurrence of skin diseases that can attack the community. In the research I did, I used the Forward Chaining Method. The system that I created is Web-based, where the system will issue a number of questions in the form of skin symptoms experienced by the user or patient and later when the patient has finished answering the question the system will process the patient's answer and finally the system will issue the answer being experienced by patients.